2013
DOI: 10.1371/journal.pone.0076144
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Biased Sequence Depth in Sequence-Independent Nucleic Acid Amplification and Optimization for Efficient Massive Parallel Sequencing

Abstract: Sequence Independent Single Primer Amplification is one of the most widely used random amplification approaches in virology for sequencing template preparation. This technique relies on oligonucleotides consisting of a 3′ random part used to prime complementary DNA synthesis and a 5′ defined tag sequence for subsequent amplification. Recently, this amplification method was combined with next generation sequencing to obtain viral sequences. However, these studies showed a biased distribution of the resulting se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…We observed that this random PCR amplification negatively impacted upon viral identification power. The observed biases in sequence distributing confirms our previous findings (Rosseel et al, 2013). Moreover, rPCR amplification increased the proportion of reads for which megablast could not find similar sequences in the NCBI nt database, suggesting the creation of amplification artefacts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We observed that this random PCR amplification negatively impacted upon viral identification power. The observed biases in sequence distributing confirms our previous findings (Rosseel et al, 2013). Moreover, rPCR amplification increased the proportion of reads for which megablast could not find similar sequences in the NCBI nt database, suggesting the creation of amplification artefacts.…”
Section: Discussionsupporting
confidence: 88%
“…Several attempts have been performed to reduce amplification introduced bias (Motley et al, 2014;Rosseel et al, 2013). Although the sequencing library preparation kit (Illumina Nextera XT) used in this study is not completely PCR-free, it supports ultra-low DNA input of only a single nanogram which eliminates the need for extra sequence independent genome amplification step.…”
Section: Discussionmentioning
confidence: 99%
“…Desert soils frequently produce suboptimal (Յ10 ng/l) viral DNA yields (66), forcing the inclusion of a random PCR amplification step for NGS library construction. The use of whole-genome amplification (WGA) by multiple-displacement amplification (MDA) or random-priming, sequence-independent, single-primer amplification (RP-SISPA) (67) almost certainly results in biased amplification of certain virus groups (68)(69)(70)(71) and prevents the accurate determination of viral abundances and diversity. While viral amplification is widely accepted as a necessity in metaviromic studies (72), we argue that amplification of virus metagenomic DNA should be avoided where possible.…”
Section: Technical Recommendations and Future Researchmentioning
confidence: 99%
“…The method has been used in conjunction with statistical algorithms to control for accuracy in studies of intrahost influenza virus diversity (5,22,23). However, the bar-coding reaction used in SISPA can be biased in unpredictable ways, resulting in uneven coverage and sensitivity across the genome (24).…”
mentioning
confidence: 99%